The Effects of the Application of Think Pair Share (TPS) on the Students’ Speaking Achievement and Anxiety - Baso Ahmad Khaeruddin; Amirullah Abduh; Sultan Baa (State University of Makassar, 2023)
The objective of this study was to determine the students’ achievement and anxiety by the implement of the think pair share method teaching speaking skill at SMA Insan Cendekia Syeh Yusuf Gowa. The study is designed in this study was quantitative with post-test and pre-test of the students tenth grade SMA Insan Cendekia Syeh Yusuf Gowa's academic year 2022-2023. The population of this study is class X was used as the sample, and it was chosen using a random selection procedure. The findings demonstrated that the mean scores of post-test of students was greater than the mean pre-test scores; the post-test mean score was (90.5333), whereas the mean score pre-test was (81.0667). The score from the alternative hypothesis (H1) is approved, hypothesis (H0) is rejected. The results of this study indicates that implementing THINK PAIR SHARE to students in Class X of SMA Insan Cendekia Syeh Yusuf Gowa was significantly improved the students’ achievement and reduce speaking anxiety. Keywords—Think Pair Share, Teaching speaking skill, Speaking achievement and anxiety